Use of cooperative learning approaches in education - Kwok, Wai Jing (2008)
Case studies method of investigation were being used to develop in this research paper. Six potential case studies on different education sector from different countries being selected for further analysis in order to answer the research question set in earlier which was to identify what are the factors that influence cooperative learning environment.